1999
DOI: 10.1038/sj.bjp.0702437
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of receptors for calcitonin gene‐related peptide and adrenomedullin on the guinea‐pig vas deferens

Abstract: 1 The receptors which mediate the e ects of calcitonin gene-related peptide (CGRP), amylin and adrenomedullin on the guinea-pig vas deferens have been investigated. 2 All three peptides cause concentration dependant inhibitions of the electrically stimulated twitch response (pD 2 s for CGRP, amylin and adrenomedullin of 7.90+0.11, 7.70+0.19 and 7.25+0.10 respectively). 3 CGRP 8 ± 37 (1 mM) and AC187 (10 mM) showed little antagonist activity against adrenomedullin. 4 Adrenomedullin 22 ± 52 by itself inhibited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…In studies with ARA in the soleus, no inverse agonism at concentrations up to 1 mM were seen [37]. Selectivity of ARA over other amylin-related peptides as an amylin antagonist has been demonstrated in the rat skeletal muscle [38] and in guinea pig vas deferens [39]. Efficacy of ARA to antagonize metabolic effects of amylin has been demonstrated in vivo in rats [40], but no direct comparisons against other amylin-related peptides have been reported.…”
Section: Methodsmentioning
confidence: 95%
“…In studies with ARA in the soleus, no inverse agonism at concentrations up to 1 mM were seen [37]. Selectivity of ARA over other amylin-related peptides as an amylin antagonist has been demonstrated in the rat skeletal muscle [38] and in guinea pig vas deferens [39]. Efficacy of ARA to antagonize metabolic effects of amylin has been demonstrated in vivo in rats [40], but no direct comparisons against other amylin-related peptides have been reported.…”
Section: Methodsmentioning
confidence: 95%
“…However, the results of these differential-affinity studies have been inconsistent [15,16], and a recent report by Rorabaugh et al [17] questioned the existence of separate CGRP2 receptors. Recent molecular data suggest that CGRP receptors use accessory proteins to form functional receptor complexes and that receptor diversity is increased by the combinatorial use of transmembrane receptors and receptor-associated proteins.…”
Section: Introductionmentioning
confidence: 97%
“…However, these differential affinity studies have been inconsistent [17,18], and a recent report by Rorabaugh et al [19] questioned the existence of separate CGRP2 receptors. Recent studies from our laboratory showed the existence of a CGRP receptor that is different from a well-characterized CGRP receptor component, calcitonin receptor-like receptor (CRLR) [20,21].…”
Section: Introductionmentioning
confidence: 98%